Association of cognitive function with frailty, nutritional status, and quality of life in older adults with mild cognitive impairment - María del Mar Carcelén-Fraile; Anabel Melguizo-Garín; Aday Infante-Guedes; Raquel Medina-Ramírez; Sandra Denche-Gil; Agustín Aibar-Almazán; Yolanda Castellote-Caballero; María del Carmen Carcelén-Fraile (PLoS ONE, 2025)
Background In older adulthood, mild cognitive impairment is an intermediate stage between normal aging and dementia, making its detection crucial. Therefore, this study aims to analyze the associations between cognitive function and frailty, nutritional status, and quality of life in older adults with mild cognitive impairment. Methods This work was conducted through a cross-sectional, analytical study involving 129 adults diagnosed with mild cognitive impairment, with a mean age of 68.07 ± 4.22. For cognitive assessment, the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Isaac Verbal Fluency Test, Trail Making Test (TMT), D2 Test of Attention (D2 Test), and Digit Symbol Substitution Test (DSST) were completed; clinical and functional status was assessed using the frailty (FRAIL), Mini Nutritional Assessment (MNA), and life quality 36-Item Short Form Survey (SF-36) questionnaires. Results Regarding overall cognitive performance, the presence of mild cognitive impairment was confirmed in the sample, as was the slowing of executive functions. Regarding selective attention, participants obtained an average of 138.30 points [SD = 4.30] in the D2 test, while the average score for processing speed measured using the DSST was 43.60 [SD = 3.50]. Regarding clinical and functional variables, the average FRAIL score was 2.26 [SD = 1.67], suggesting a high prevalence of frailty and pre-frailty; the average nutritional status was 27.91 [SD = 1.88], a range of adequate nutritional status. Finally, quality of life showed an average of 61.40 [SD = 14.87], indicating a moderate level. Discussion This study shows that frailty, nutritional status, and quality of life are closely related to mild cognitive impairment. These results reinforce the need for early and multidimensional interventions that contribute to preserving the quality of life.